Kesantunan Berbahasa Pada Juru Bicara Elpi Nazmuzzaman Dalam Proses Pencarian Eril Dan Rekomendasinya Sebagai Bahan Ajar - Fadli, Egi Ahmad; Sutri, Sutri; Sugiarti, Dewi Herlina (Jurnal Ilmiah Wahana Pendidikan, 2024)
Language politeness is one part of the science of pragmatics based on the principles of politeness. Language politeness plays a role in maintaining and upholding one's self-image. This belief arises because most utterances have the potential of both the speaker and the speech partner, and language politeness aims to reduce threats to self-image through better communication. Therefore, politeness can be explained as an effort to avoid conflict between the speaker and the interlocutor in the communication process. The aim of this research is to describe the principles of language politeness used by Elpi Nazmuzzaman spokesperson in the Eril Search Process and make recommendations for the results of the analysis as teaching materials for Indonesian language learning in Class VIII Middle Schools. This research uses the polite principles of Lecch's theory by applying a qualitative descriptive approach. The results of the research from the 3 videos used, found that a total of 35 utterances were used in total and 29 utterances that complied with the maxims of politeness were more widely used, while 6 utterances violated the maxims of politeness. Based on the data, maxims of praise and maxims of agreement are the types of maxims that are often used by Elpi Nazmuzzaman in speeches. The results of the research carried out will be recommended as teaching material in the form of digital handouts on speech text material at junior high school level. Teaching materials will be adapted to Phase D class VIII with CP writing elements. This teaching material can be used by teachers during the learning process regarding speech texts and helps students understand the concept of speeches, the structure of speech texts, and students' ability to judge whether the sentences spoken by the speaker are polite or not.